2017
DOI: 10.1371/journal.pone.0183835
|View full text |Cite
|
Sign up to set email alerts
|

Serum calcium, alkaline phosphotase and hemoglobin as risk factors for bone metastases in bladder cancer

Abstract: Early detection of bone metastases is helpful for the treatment of bladder cancer (BC). In this study, we investigated the potential risk factors for bone metastasis in newly diagnosed patients with BC. A total of 902 patients diagnosed with BC between January 2000 and August 2016 were retrospectively reviewed. Of these patient, 50 (5.5%) were identified with bone metastasis. The serum levels of alkaline phosphatase (ALP) and calcium were significantly higher in patients with bone metastases than those without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 17 publications
(17 reference statements)
0
38
1
Order By: Relevance
“…In other words, pre-treatment ALP values may be a useful biomarker in the choice of treatment, even in early metastatic PC. The prognostic value of ALP has been shown in various solid malignancies with bone metastasis [11][12][13]. However, while there is a biological rationale underlying this association, the exact mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, pre-treatment ALP values may be a useful biomarker in the choice of treatment, even in early metastatic PC. The prognostic value of ALP has been shown in various solid malignancies with bone metastasis [11][12][13]. However, while there is a biological rationale underlying this association, the exact mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…ALP is a glycoprotein derived from bones, liver, kidney, or placenta that has been shown to be elevated and of prognostic value for various malignancies [10][11][12][13]. In PC, ALP has been shown to be of prognostic value in CRPCreflecting disease outcome, independent of therapy [14].…”
Section: Introductionmentioning
confidence: 99%
“…The high ALP level has been reported related to the poor survival in colorectal cancer 71. The elevation of ALP is also an independent risk factor in the bone metastasis of gastric cancer and bladder cancer 72,73. However, the underlying mechanisms of ALP in patients with PCa remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…18 What is more, tumor markers can be used to predict cancer metastasis, which is of great significance. For, example, Huang et al 19 observed that ALP and HB were risk factors for bone metastases in patients with bladder cancer. And CA-125 might play an important role in tumor metastasis, and could be thought as an independent risk factor for bone metastases in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%